Activity of the novel mTOR inhibitor Torin-2 in B-precursor acute lymphoblastic leukemia and its therapeutic potential to prevent Akt reactivation - Simioni, Carolina (Oncotarget, 2014)
The PI3K/Akt/mTOR signaling cascade is a key regulatory pathway controlling cell growth and survival, and its dysregulation is a reported feature of B-precursor acute lymphoblastic leukemia (B-pre ALL). Torin-2 is a novel, second-generation ATP-competitive inhibitor that is potent and selective for mTOR with a superior pharmacokinetic profile to previous inhibitors. It has been shown that Torin-2 displayed dramatic antiproliferative activity across a panel of cancer cell lines. To investigate if Torin-2 could represent a new option for the treatment of B-pre ALL, we tested its activity on a panel of B-pre ALL cell lines. In all of them Torin-2 showed a powerful cytotoxic activity, inhibiting the growth of each cell line in a dose-dependent manner, with an IC(50) in the nanomolar range. Torin-2 caused both apoptosis and autophagy, induced cell cycle arrest in G(0)/G(1) phase and affected both mTORC1 and mTORC2 activities as assessed by their specific substrate dephosphorylation. Torin-2 alone suppressed feedback activation of PI3K/Akt, whereas the mTORC1 inhibitor RAD001 required the addition of the Akt inhibitor MK-2206 to achieve the same effect. These pharmacological strategies targeting PI3K/Akt/mTOR at different points of the signaling pathway cascade might represent a new promising therapeutic strategy for treatment of B-pre ALL patients.